Modeling Potential Dispersal Routes for Giant Pandas in Their Key Distribution Area of the Qinling Mountains, China - Liu, Xuehua; Liu, Lanmei; Liu, Linna; Jin, Xuelin; Songer, Melissa (Frontiers in Ecology and Evolution, 2021)
The national surveys on giant panda populations and habitat quality have shown a high-density population of giant pandas in the Qinling Mountains, China. We investigated their core distribution area of the Qinling Mountains to model and identify the potential dispersal routes for giant pandas among five adjacent nature reserves (NR). We hypothesized that giant pandas will spread to neighboring areas when the population of the species keeps increasing. Habitat suitability was firstly evaluated based on environmental and disturbance factors. We then identified source and sink patches for giant pandas’ dispersal. Further, Minimum Cumulative Resistance (MCR) model was applied to calculate cost of movement. Finally, the Current Theory was used to model linkages between source patches and sink patches to explore potential dispersal routes of giant pandas. Our results showed that (1) three large source patches and eight potential sink patches were identified; (2) 14 corridors were predicted for giant pandas dispersing from source patches to the neighboring areas; (3) through the predicted corridors, the giant pandas in the source patches could disperse to the west, the south and the east sink patches. Our research revealed possible directional patterns for giant pandas’ dispersal in their core distribution area of the Qinling Mountains, and can provide the strong recommendations in policy and conservation strategies for improving giant panda habitat management in those identified sink patches and also dispersal corridors.